Synthesis and Characterization of some Mixed Ligand Complexes Containing (8-hydroxyquinoline) and (2 - picoline) with some Metal Ions (Baghdad Science Journal, 2013)
Complexes of some metal ions ( Mn(I? ) , Co(??) , Ni(??) ,Cu (??) , Zn(I?) , Cd (??) , and Hg(??) ) with 8-hydroxyquinoline (Oxine) and 2- Picoline (2-pic ) have been synthesized and characterized on the basis of their FT-IR. and Uv-visible spectroscopy ,atomic absorption molar conductivity measurements and magnetic susceptibility ,from the results obtained the following general formula has been given for prepared complexes [M (oxine)2 (2-pic)2]where M = M(??) = Mn , Co , Ni , Cu , Zn , Cd , Hg(oxine)- = ionic ligand 8-hydroxyquinolin (oxinato)(2- pic) = 2- picoline